The Diagnosis, Risk Stratification, and Treatment of Brugada Syndrome - Steinfurt, Johannes (Dtsch Arztebl Int, 2015)
BACKGROUND: Brugada syndrome (BrS) is among the more common familial arrhythmia syndromes, with an estimated prevalence of 1 to 5 per 10 000 persons. It is characterized by a right ventricular conduction delay, dynamic or persistent ST-segment elevations in the precordial leads V(1–3), and an elevated risk of syncope and sudden cardiac death in young adults without structural heart disease. METHODS: This article is based on original and review articles on BrS that appeared in English from 2010 onward and were retrieved by a selective search in PubMed, with special attention to international consensus publications on inherited arrhythmogenic diseases. RESULTS: According to the new diagnostic criteria, the diagnosis of BrS requires typical ECG changes in only one precordial lead. This will likely increase sensitivity, but may also lead to an increase in asymptomatic patients. Established risk markers include sudden cardiac arrest and a spontaneous type 1 ECG with arrhythmic syncope. Patients with these findings benefit from the implantation of a cardioverter-defibrillator. There is no validated algorithm for risk stratification of asymptomatic patients. Because of the low prevalence of BrS, there have been no randomized controlled trials (RCTs) in this disease, and all recommendations are based on expert opinion. BrS is usually inherited in an autosomal dominant manner. Recently discovered gene polymorphisms modify the risk of BrS, challenging the conception of BrS as a monogenetic disease. Electro-anatomic mapping studies have revealed, for the first time, an arrhythmogenic substrate over the right ventricular outflow tract in BrS patients. CONCLUSION: BrS is one important differential diagnosis to consider in patients presenting with syncope or sudden cardiac arrest. The goal of current research is to achieve a deeper understanding of the genetic and electrophysiological changes underlying BrS. Further insights in these areas will probably enable better risk stratification of asymptomatic BrS patients in the future.